2018
DOI: 10.3174/ajnr.a5866
|View full text |Cite
|
Sign up to set email alerts
|

How to Size Intracranial Aneurysms: A Phantom Study of Invasive and Noninvasive Methods

Abstract: BACKGROUND AND PURPOSE: Endovascular treatment of intracranial aneurysms has relevantly changed over the past decades. Multiple new devices such as intrasaccular flow diverters have broadened the treatment spectrum but require very exact aneurysm sizing. In this study, we investigated multidetector and flat panel angiographic CT and digital subtraction imaging as well as different postprocessing methods (multiplanar reconstruction, volume-rendering technique, 3D DSA, and conventional 2D angiography) for their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Yet, problems may arise with bifurcation aneurysms and occlusion of side branches. 5 Endo-saccular flow disruption devices such as the WEB (Microvention) or the Contour device are deployed within the aneurysm, intending to create a doubling effect with intra-aneurysmal flow disruption The Neuroradiology Journal 35 (3) and induction of thrombosis followed by a remodelling of the parent artery. 1 The mesh positioned at the aneurysm neck can lead to neo-endothelial overgrowth, making them well suited for wide-necked bifurcation aneurysms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, problems may arise with bifurcation aneurysms and occlusion of side branches. 5 Endo-saccular flow disruption devices such as the WEB (Microvention) or the Contour device are deployed within the aneurysm, intending to create a doubling effect with intra-aneurysmal flow disruption The Neuroradiology Journal 35 (3) and induction of thrombosis followed by a remodelling of the parent artery. 1 The mesh positioned at the aneurysm neck can lead to neo-endothelial overgrowth, making them well suited for wide-necked bifurcation aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…After diagnostic runs, 3D digital subtraction angiography was performed, and working projections were chosen accordingly. 3 A 0.021 00 Headway TM catheter (Microvention) and a 0.014 00 Synchro microwire (Stryker, Kalamazoo, MI) were used for catheterisation of the aneurysm. The device was oversized to the equatorial plane of the aneurysm, as reported previously.…”
Section: Procedural Techniquementioning
confidence: 99%
“…Therefore, how to size the intracranial aneurysm has been disputed and discussed over the past years. A study by Behme et al reported that the most exact aneurysm measurement can be achieved on a 2D DSA image with a short objective-to-detector distance adjusted according to a previous 3D run [ 11 ]. Meanwhile, the AngioSuite software is proposed to be an accurate method to calculate aneurysm volumes in comparison with AngioCalc or other specialized software based on rotational angiography [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true for the exact volume calculation of TVIAs due to their extremely limited space for stable coil deployment. Until recently, how TVIA volume should be measured and calculated reaches no consensus [ 11 ]. Therefore, based on the guiding role of TVIA volume measuring in endovascular treatment, we propose that the volume of TVIAs is a superior index over diameter in describing the characteristic of a cystic lesion, especially for those aneurysms with irregular appearance.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not as good as cerebral angiography in identifying the size or location of the aneurysm [ 10 , 11 ]. DSA only retains the vascular images, which can realize the positioning of vascular lesions and has huge advantages in judging the direction of blood flow [ 12 , 13 ]. MRA uses electromagnetic waves to generate a two-dimensional or three-dimensional structure image.…”
Section: Introductionmentioning
confidence: 99%